Between the Cross and the Parousia Consummation: An Analysis of Paul’s Love Ethics and Its Contemporary Lessons - Letšosa, Rantoa Simon (Journal of early Christian history, 2025)
Scriptural accounts demonstrate that by Jesus’s sacrificial death and transformation by the Holy Spirit, God’s salvation became available in Christ, who gives new life and produces a new reality characterised by developed conformity to the royal law of love. Paul’s ethics within the context of his training as a Pharisee, which schooled him in the rigid demands of the law, was transformed by his union with Jesus Christ, who fulfilled the law by his death and the power of the Holy Spirit. Consequently, when the Spirit is present, the new life becomes the beginning of salvation and is characterised as a blessing of a new age. This is what Paul’s Christocentric ethics of love is all about: Spirit- driven, love-focused, new creation-based, and eschatologically oriented. This article examined Paul’s love ethics under five theological principles that influenced his philosophy. The article further viewed Paul’s love ethics from the perspectives of early Christians such as Augustine, Aquinas, Chrysostom, and Luther. Further contemporary thoughts were attempted before the discussion snowballed to issues of racial, social, and economic justice as well as cohesion. The article concluded with lessons showing that with love rightly ordered (Ordo amoris), humans can coexist in society.